Формирование функциональной грамотности младших школьников - Мишура, О.А. (My University, 2016)
0f limits renovation state compulsory standard of education development functional grammar of children determine one’s position to get aims of education. to expose influence receptions of development of critical though and training dialogue to development functional grammar. the analysis of literature, observation, questionnaires, monitoring. the forming functional grammar of children. to use dialogue forms of the lesson allow to us development functional grammar, on the result organize of competence- orienting personality, including communicative and social- adapting personality.
Keywords: Functional grammar; individual studies activity; dialogue of teaching; to develop critic thought; of competence-oriented personality